Economic Analysis and Performance of PV Plants: An Application in Kurdistan Region of Iraq - Bamisile, Olusola; Olubiyo, Foyin; Dagbasi, Mustafa; Adun, Humphrey; Wole-Osho, Ifeoluwa (International Journal of Renewable Energy Development, 2019)
In this study, photovoltaic (PV) technology development over the years is reviewed. The use of PV power plants to solve inadequate power supply in Kurdistan is also analysed. PV power application is one of the most developed renewable energy applications but still not commercialized in somw countries. In this paper, three different locations will be evaluated in Kurdistan for PV plant installation. The research will investigate the best location for PV plant installation in Kurdistan, check the viability of the proposed plants and compare the performance of a fixed and a double axis tracking system. A 10 MW PV plant is developed and simulated based on economic terms. The results from the analysis shows that the simple payback period for a 10 MW PV plant in all the locations considered is between 6.8 and 7.2 years. Also, the installation with two-axis tracking system gave the lowest simple payback period (6.8 years). The PV plant is viable considering other economic indicators like; IRR, NPV, annual life cycle savings and BCR. The yearly savings of the system for one of the locations considered is US$1,573,327 with a dual axis tracking system. Â©2019. CBIORE-IJRED. All rights reserved